Consequências da violência sexual perpetrada na juventude - Costa, Vanessa Fontana da (2018)
Nowadays sexual violence (SV) is considered a public health problem. SV perpetrated in youth must increasingly be discussed in current society, because of its high level of occurrence and the seriousness of the consequences suffered by individuals who have been through it. The lack of specific public policies is another reason for the discussion, since violence against young adults does not have much investigation, perhaps due to few reports or to the view of some acts as commonplace of this age group. Therefore, the dissertation aims to discuss the subject of SV perpetrated in youth, trying to understand its consequences and to think about some possibilities of answers or health actions before it. This qualitative research is based on an explanatory case study, a method widely used in social researches that seek to perceive an observable phenomenon in a deeper way. In order to understand the consequences of sexual violence against young persons, different data sources were used, looking for integrating the view from who has lived such phenomenon and from who works professionally with this issue. Some semi-structured interviews with both participants were conducted and ethical principles in research with human beings were observed. The data collected are organized into two units of analysis that have already led two articles entitled “‘I bring with me’: consequences of sexual violence perpetrated in youth” and “‘Hold this pain and let’s turn this into a fight’: health actions before sexual violence perpetrated in youth”. These articles point out the importance of the discussion about gender issues that can influence not only occurrences of SV, but also possible effects on those who have suffered this kind of violence. Although consequences of SV depend on many factors, this violence certainly affects all aspects of life, directly or indirectly. Gathering information about SV seems to be a key factor for dealing with the situation, from more practical knowledge about some procedures which can be taken after a case of violence to a definition and a characterization of this violence. The Internet has been a great instrument to obtain information about SV, for it allows researches on this subject without direct exposure and it facilitates access to feminist discourses, which have been a leading player in discussions about gender violence and women’s struggle for rights. Realizing SV as a public health problem is of utmost importance, as well as promoting the creation of public policies that increase and support actions to prevent and promote health.